Kepatuhan Wajib Pajak UMKM dalam Pelaporan Pajak: Studi Kualitatif Kabupaten Polewali Mandar - Meliana; Dewi, Ni Made Sintya Surya (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
This study aims to analyze the compliance of MSME Taxpayers in tax reporting in Polewali Mandar Regency. The main focus of this study is to understand the factors that influence tax reporting compliance among MSME actors, including taxpayer understanding, awareness of tax regulations, and support from local governments. Lack of knowledge and limited resources are often the main obstacles to proper tax reporting. This study recommends a tax education program for MSMEs, simplification of reporting procedures, and improvement of MSME-friendly tax service facilities to improve compliance. With this support, it is hoped that MSME Taxpayer compliance in Polewali Mandar Regency can increase significantly, encouraging regional economic growth through optimal tax contributions.